Manganese uptake by mouse liver subcellular fractions. I. Effect of ferricions - Bonilla, Ernesto (Investigación Clínica, 2013)
It has been shown that intraperitoneally Â¡njected 54Mn concentrates primarily in mitochondrial and nuclear fractions of hepatic cells. The microsomal and the supernatant represented 59% and 42% respectively of the mitochondrial uptake. This pattern of distribution did not change with time and it was mantained for at least 5 days after injection. The in rítro studies revealed that 1 mM FeCI 3 produced a significant increase of MMn uptake in each one of the subcellular fractions. It is believed that Fe 3 + acts as oxidant in the following oxidation-reduction mechanism: 1) Mn2 + (dissociable) -1e ---> Mn3 + (bound);2) Fe3 + + le .. Fe2 +.